ANALISIS PREDIKSI KEBANGKRUTAN PADA PT FKS FOOD SEJAHTERA TBK PERIODE 2018-2022 - Puteri, Adelia; Afrizawati, Afrizawati; Purnama Sari, Keti (Jurnal Riset Terapan Akuntansi, 2024)
The purpose of this study was to analyze the prediction of bankruptcy using the Grover and Taffler model at PT FKS Food Sejahtera Tbk for the period 2018-2022. In this research, both models of bankruptcy prediction analysis are measured through the level of accuracy to determine the highest accuracy in the prediction model. Descriptive research method with a quantitative approach and using secondary data in the form of annual financial statements, namely the statement of financial position and income statement from PT FKS Food Sejahtera Tbk for the period 2018-2022. The results of this study indicate that the Grover model is predicted in 2018,2021 and 2022 to experience bankruptcy while 2019-2020 is predicted to be healthy and for the Taffler model in 2018, 2019, 2020 and 2021, PT FKS Food Sejahtera Tbk were predicted to be healthy or not bankrupt. While in 2022 the Taffler model predicts that the condition of the company is in a gray Area or prone to bankruptcy for the company. The accuracy level of Grover bankruptcy prediction analysis model is 40% and Taffler is 80% where Taffler model is the most accurate prediction model in this study. Keywords: Bankruptcy, Grover, Taffler.